(untitled) (World Bulletin of Public Health, 2024)
In the modern world, human health is increasingly influenced by various properties and qualities of environmental factors. About 85% of all diseases in the modern world are associated with unfavorable environmental conditions caused by everyday human production activities. Today, new unstudied diseases are appearing in the world, the causes of which cannot be established. This article provides information on the effect of dust in atmospheric air on human health, types and sizes of dust in industry and production, and the effect of dust on the upper respiratory tract.